Defining the phenotype of young adults with family histories of alcohol and other substance use disorders: Studies from the family health patterns project. (February 2018) - Acheson, Ashley; Vincent, Andrea S.; Cohoon, Andrew J.; Lovallo, William R.
Abstract: Individuals with a family history of alcohol and other drug use disorders (FH +) are at increased risk for developing substance use disorders themselves relative to those with no such histories (FH −). Here we sought to identify key characteristics associated with FH + status and alcohol and other drug use disorder status in a large cohort of FH + and FH − young adults. We conducted principal component analyses on demographic, temperament, and cognitive measures differentiating 506 FH + and 528 FH − young adults. Three principal components were identified, and these component scores were then used to predict the odds of being FH + and the odds of having an alcohol or other drug use disorder. Component 1 consisted of measures indexing internalizing traits, with higher component scores indicating greater depressive, anxious, and emotional instability tendencies. Component 2 consisted of measures of externalizing traits as well as exposure to early life adversity (ELA), with higher scores indicating less impulse control, more antisocial behavior, and greater ELA exposure. Component 3 consisted of estimated intelligence, delay discounting, and demographic characteristics, with higher scores indicating lower estimated intelligence, greater discounting of delayed rewards, less education, and lower childhood socioeconomic status. For each 1-point increase in the Component 1, 2, and 3 scores, the odds of being classified FH + increased by 2%, 8%, and 4%, respectively. Similar findings were observed when individuals with alcohol or other drug use disorders were removed from the analyses. Finally, greater Component 2 scores were also associated with increased odds of having an alcohol or other drug use disorder. Collectively, these findings provide a more comprehensive understanding of the FH + phenotype in young adults and help form a basis for further studies on biological mechanisms underlying risk for substance use disorders. The present findings also provide further support for a prominent role of ELA in promoting risk for problem alcohol and other drug use. Highlights: Measures affected by family history of substance use disorders were compared. From these measures three principal components were identified. An externalizing behaviors and adversity component best predicted family history. This same component also best predicted substance use disorders.